Portfolio of Péter István Balogh, Sándor Mohácsi and the Studio 73 - Balogh, Péter István; Mohácsi, Sándor (4D Journal of Landscape Architecture and Garden Art, 2012)
Our design studio was established in 2001 with the mission of helping develop – with our common activities – a high quality human environment that serves the local community, economy and culture. We do believe in the key role of landscape architecture and its integrated approaches in the improvement of the liveability and sustainability of the settlements – that’s why we develop our conceptions in this context, too. While designing details we aspire to use natural solutions in both esthetical and technical meaning.